The Influence of Budget Management and the Internal Audit Unit on the Effectiveness of Asset Management at the Youth and Sports Office of Sigi Regency - Nur Syafira Sahido; Burhanuddin; Suwedy; Ali Supriadi (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
The purpose of the study is to find out and analyze the influence of budget management and internal supervision units on the effectiveness of asset management at the Sigi Regency Youth and Sports Office. The analysis tool in this study uses multiple regression. The results of the study obtained F_{count} were 11.344 while the value of F_{Table} ( α 0.05), numerator = 2 and denumarator = 29 was 1.699. So F_{count} > F_{Table} ( α 0.05) thus, Ho is rejected and Ha is accepted. The results of the rejection of Ho's hypothesis show that the existing evidence supports an alternative hypothesis, namely Ha, which states that there is an influence of Budget Management and Internal Oversight Units together on the Effectiveness of Asset Management at the Sigi Regency Youth and Sports Office.